2019
DOI: 10.3390/cancers11020171
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptide TP4 Induces ROS-Mediated Necrosis by Triggering Mitochondrial Dysfunction in Wild-Type and Mutant p53 Glioblastoma Cells

Abstract: Antimicrobial peptide tilapia piscidin 4 (TP4) from Oreochromis niloticus exhibits potent bactericidal and anti-tumorigenic effects. In a variety of cancers, the mutation status of p53 is a decisive factor for therapeutic sensitivity. Therefore, we investigated the impact of p53 status on TP4-induced cytotoxicity in glioblastoma cell lines and the molecular mechanisms that govern cytotoxic effects. Both U87MG (wild-type/WT p53) and U251 (mutant p53) glioblastoma cell lines were sensitive to TP4-induced cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 69 publications
0
36
1
Order By: Relevance
“…Moreover, CUL7 overexpression promoted proliferation in glioma cells in our study. Although many previous studies have reported that CUL7 promoted tumorigenesis by suppressing P53 [10,40,41], CUL7 also promoted the proliferation of U251, a glioma cell line with mutated p53 [42], in our study; this indicates that CUL7 could have other independent pathways to promote the development of glioma. In this way, to attain the potential molecular mechanisms by which CUL7 promotes glioma development, we detected the expression changes of some key mediators of cell proliferation and apoptosis, including p21, p27, cyclin D1, CDK4, cyclin E1 and CDK2.…”
Section: Discussioncontrasting
confidence: 79%
“…Moreover, CUL7 overexpression promoted proliferation in glioma cells in our study. Although many previous studies have reported that CUL7 promoted tumorigenesis by suppressing P53 [10,40,41], CUL7 also promoted the proliferation of U251, a glioma cell line with mutated p53 [42], in our study; this indicates that CUL7 could have other independent pathways to promote the development of glioma. In this way, to attain the potential molecular mechanisms by which CUL7 promotes glioma development, we detected the expression changes of some key mediators of cell proliferation and apoptosis, including p21, p27, cyclin D1, CDK4, cyclin E1 and CDK2.…”
Section: Discussioncontrasting
confidence: 79%
“…In addition, TP3 is important to the development of antibacterial drug research. To our best knowledge, there was no anti‐cancer research on TP3, while TP4 has been reported to have anti‐cancer activities 6,53 . The sequence between TP3 (FIHHIIGGLFSVGKHIHSLIHGH) and TP4 (FIHHIIGGLFSAGKAIHRLIRRRRR) is similar and both peptides have amphiphilic, α‐helical, cationic characteristics, suggesting that TP3 may have the potential to treat glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of infiltration is related to the degradation of the extracellular matrix (ECM) within the TME. In particular, the process breaks down the basement membrane of the ECM, resulting in the disturbance of the TME 6 . The ECM is a three‐dimensional (3D) extracellular network consisting of macromolecules (eg proteoglycan, proteins including collagens, etc) that support cell mass 7 and surround blood vessels in all tissues 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Various cell death pathways can be induced by antimicrobial peptides, such as apoptosis and necrosis [15,16]. To determine which cell death pathway is involved in epi-1-mediated death of synovial sarcoma cells, whole-cell lysates were collected from epi-1-and staurosporine (stau; apoptosis inducer)-treated SW982 cells, followed by immunoblotting with a caspase-3 antibody.…”
Section: Epi-1 Triggers Caspase-independent Cell Death In Sw982 Cellsmentioning
confidence: 99%
“…Cytotoxicity was determined as previously described [15,38]. Briefly, after stimulation, culture supernatant and attached cells were collected using trypsin, and viable cell count was calculated by trypan blue exclusion assay.…”
Section: Cytotoxic Assaymentioning
confidence: 99%